2021
DOI: 10.3390/plants10091776
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Endophytic Bacillus cereus T4S and Its Plant Growth-Promoting Traits

Abstract: Insights into plant endophytic microbes and their exploration in agriculture have provided opportunities for sustainable plant health and food safety. Notable endophytic Bacillus species with plant growth-promoting traits have been documented; nevertheless, information on genome analysis of B. cereus associated with the sunflower in South Africa has not been studied. Therefore, we present whole-genome sequence of agriculturally important B. cereus strain T4S isolated from sunflower plants. The NextSeq Illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 74 publications
3
22
0
Order By: Relevance
“… Ashraf, Bano & Ali (2019) isolated Bacillus cereus from wheat rhizosphere and reported its biofertilizer effect on maize. Recently, Adeleke, Ayangbenro & Babalola (2021) also reported that Bacillus cereus associated with sunflower have potential to produce PGP substances and improve plant growth. Xu et al (2022) isolated Bacillus subtilis from the soil of wheat rhizosphere and showed the antagonism effect against Fusarium crown rot fungal disease of wheat and increase the fresh and dry weight of the wheat.…”
Section: Discussionmentioning
confidence: 99%
“… Ashraf, Bano & Ali (2019) isolated Bacillus cereus from wheat rhizosphere and reported its biofertilizer effect on maize. Recently, Adeleke, Ayangbenro & Babalola (2021) also reported that Bacillus cereus associated with sunflower have potential to produce PGP substances and improve plant growth. Xu et al (2022) isolated Bacillus subtilis from the soil of wheat rhizosphere and showed the antagonism effect against Fusarium crown rot fungal disease of wheat and increase the fresh and dry weight of the wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that the HGS7 strain conferred greater drought tolerance to mulberry trees. The presence of these genes confers the ability to defend against oxidative stress, thus contributing to microbial colonization and survival required for improved plant growth ( Adeleke et al, 2021 ). The presently isolated HGS7 strain exhibited extraordinary capability to endure various pH, temperature, and salt conditions in vitro , thus suggesting the potential ability to stimulate plant growth in adverse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, petrobactin production is not exclusive to pathogenic isolates; indeed, numerous innocuous soil-residing isolates are also capable of producing this siderophore [ 57 ]. For example, genome analysis of the endophytic strain Bacillus cereus T4S, believed to possess plant growth-promoting traits, revealed the presence of the same petrobactin BCG [ 58 ]. Thus, it can be hypothesized that this endophytic strain might play a role in encouraging plant growth by means of the acquisition of iron and in protecting its host through the synthesis of secondary metabolites with recognized antibiotic properties [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%